2017
DOI: 10.1159/000454987
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Colonic Perforation due to Ventriculoperitoneal Shunt: Case Report and Literature Review

Abstract: Abordagem endoscópica de perfuração do cólon por cateter de derivação ventrículo-peritoneal: caso clínico e revisão da literatura Palavras Chave Derivação ventrículo-peritoneal · perfuração cólica · colonoscopia ResumoOs autores descrevem o caso de uma mulher de 42 anos com perfuração do cólon por cateter de derivação ventrí-culo-peritoneal (DVP) colocado 28 anos antes. No contexto de meningite aguda a Escherichia coli , o estudo complementar com tomografia computadorizada abdominal identificou a extremidade d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Alves et al reported a case of symptomatic colonic perforation 28 years after the initial shunt placement presenting with acute meningitis. In this case, during endoscopic exploration, chronic fibrous tissue around the site where the catheter had entered the colon was observed; therefore, the spillage of bowel contents into the peritoneal cavity was prevented [14]. These papers indicate that patients with intracerebral sepsis due to enteric bacteria must be assessed for BPPC [6,15].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Alves et al reported a case of symptomatic colonic perforation 28 years after the initial shunt placement presenting with acute meningitis. In this case, during endoscopic exploration, chronic fibrous tissue around the site where the catheter had entered the colon was observed; therefore, the spillage of bowel contents into the peritoneal cavity was prevented [14]. These papers indicate that patients with intracerebral sepsis due to enteric bacteria must be assessed for BPPC [6,15].…”
Section: Discussionmentioning
confidence: 85%
“…In no patient, BPPC occurred >8 years after shunt placement [6]. However, symptomatic BPPC > 20 years after initial shunt placement is extremely rarely reported [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several contributing factors that affect the complications in anal extrusion of peritoneal catheter are thin bowel wall in children (11), sharp and stiff end of VP shunt (5), distal tip of ventricular-peritoneal catheter placement with trocar (10), long peritoneal catheters chronic irritation caused by shunt (12) previous surgery, infection, and silicone allergy (13). Children of families with low socioeconomic status and suffering from malnutrition also have an increased risk of an anal extrusion VP shunt (10).…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with a variety of complications, which occur in an average of 23.8% of cases. A very small portion of these complications is distal shunt migration with gastrointestinal perforation [1,2].…”
Section: Introductionmentioning
confidence: 99%